Various Ages and Slopes of Oil Palm in the Bilah Sub-Das, Labuhanbatu Regency on the Physical Properties of the Soil - Fitra Syawal Harahap; Hilwa Walida; Zulkifli Musannip Effendi Siregar (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Oil palm (Elaeis guineensis Jacq.) cultivation is a primary economic sector in Indonesia, with North Sumatra being a leading production region. However, the sector's expansion, exemplified in the Bilah Sub-watershed, Labuhanbatu, has raised concerns regarding the deterioration of soil physical properties, posing a risk to long-term agricultural sustainability. While plantation age and topographic slope are identified as key influencing factors, their interactive effects remain inadequately examined. This study, therefore, aimed to analyze the differences in soil physical characteristics across varying oil palm ages and slope gradients. Conducted from May to August 2025 in Negeri Lama Village, the research employed a factorial design with three plantation ages (newly planted, 5, and 12 years) and three slope classes (0-3, 3-8, and 8-15%). Parameters assessed included soil texture, organic matter content, porosity, water content, and permeability. The results demonstrate that increasing plantation age positively correlates with improved soil conditions, marked by higher organic matter, porosity, water content, and permeability, alongside reduced bulk density. Conversely, steeper slopes significantly degrade these same properties. The study underscores the critical interaction between these two factors. Its importance for the oil palm industry lies in providing empirical evidence for developing site-specific soil management strategies. The findings advocate for enhanced conservation practices, particularly on slopes exceeding 8%, to mitigate degradation and ensure the ecological and economic sustainability of this vital commodity system.